FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA (SHU) PADA KOPERASI SYARIAH DI SURABAYA PADA PERIODE TAHUN 2014-2018 - Anindya Nur Hidayati; Dian Filianti (Universitas Airlangga, 2019)
This study aims to analyze the influence of the number of members, own capital, and External capital on the Remaining Business Result (SHU) in Islamic cooperatives in Surabaya for the period 2014-2018. This study uses a quantitative approach. The subject used is the Sharia Cooperative in the Surabaya area with an annual period of 2014-2018. The method used in this study is a panel data regression analysis model that is processed using Stata software. Based on the results of the analysis it is shown that the variable number of members and own capital partially have a significant positive effect on SHU. Whereas,External capital has a negative significant effect on SHU. Nevertheless, simultaneously the number of members, own capital, and External capital have a significant effect on the Remaining Business Result (SHU).Keywords: Remaining Business Result (SHU), Number of Members, Own Capital, External CapitalREFFERENCESAnggraini, Novi Hasti. 2009. “Analisis Faktor-Faktor Yang Mempengaruhi Sisa Hasil Usaha Koperasi Pegawai Negeri Di Kota Surakarta Tahun 2007”. Universitas Sebelas Maret (Online). eprints.uns.ac.id, diakses pada 27 Juni 2017.Anshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metode Penelitian Kuantitatif. Surabaya: Pusat Penerbitan dan Percetakan Unair (AUP).Arifin, Zainul. 2009. Dasar-Dasar Manajemen Bank Syariah. Jakarta: Raja Grafindo Persada.Azim, Amin. 1987. Perkoperasian Indonesia. Yogyakarta: BPFEBaswir, Revrisond. 2000. Koperasi Indonesia. Yogyakarta: BPFE-YOGYAKARTA.Buchori, Nur Syamsudin. 2009. Koperasi Syariah. Sidoarjo: Masmedia Buana Pustaka.Departemen Koperasi. Undang-Undang Republik Indonesia No. 25 Tahun 1992. Tentang Perkoperasian.Dewan Syariah Nasional. 2000. Fatwa No. 15/DSN-MUI/IX/2000. (Online). www.dsnmui.or.id, diakses pada 29 Januari 2019.Firdaus, Muhammad dan Agus Endi Susanto. 2004. Perkoperasian Sejarah,Teori dan Praktek. Bogor: Ghalia Indonesia.Ghozali, Imam. 2006. Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Hendrojogi. 1998. Koperasi Asas-Asas Teori dan Praktek. Jakarta: PT Raja Grafindo Persada.Nazir, Mohammad. 1983. Metode Penelitian. Jakarta: Ghalia Indonesia.Sagimun. 1983. Koperasi Indonesia. Jakarta: Departemen Pendidikan dan Kebudayaan.Sedarmayanti, Syarifudin Hidayat. 2002. Metodologi Penelitian. Bandung: Mandar Maju.Sholihin, Ahmad Ifham. 2008. Buku Pintar Ekonomi Syariah. Jakarta: PT Gramedia Pustaka Utama.Sitio, Arifin dan Halomoan Tamba. 2001. Koperasi: Teori dan Praktek. Jakarta: Erlangga.Suwito, K. Tjilik dkk. 1991. Peran Serta Anggota dan Pengembangan Koperasi Suatu Pengkajian Fungsional di Kotamadia Dati II Surakarta. Laporan Penelitian Mandiri. Universitas Sebelas Maret Surakarta.Widiyanti, Ninik dan YW Sunindhia, SH. 1989. Koperasi dan Perekonomian Indonesia. Jakarta: PT Bina Aksara.Winarko, Sigit Puji. 2014. “Pengaruh Modal Sendiri, Jumlah Anggota, dan Aset Terhadap Sisa Hasil Usaha Pada Koperasi di Kota Kediri”. Nusantara Of Research (Online). efektor.unpkediri.ac.id, diakses pada 1 Februari 2019.